Study on Irrigation Water Quality in the Rift Valley Areas of Awash River Basin, Ethiopia - Zeyede Aregahegn; Mulate Zerihun (Applied and Environmental Soil Science)
Awash River water has been impaired by various types of pollution owing to waste released from different socioeconomic activities in its basin. This study aimed to evaluate the water quality of the Awash River and its tributaries in the basin used for irrigation purposes. Sampling sites were identified based on the pollution sources, accessibility, and land-use coverage. A total of 17 sampling sites were chosen along the Awash River, and samplings were collected four times a year through different seasons. The overall water quality and suitability for irrigation are explained using multiple water quality parameters such as pH, EC, SAR, RSC, Na+, K+, Ca + Mg, CO32−, HCO3−, and Cl−. The obtained results showed that all quality parameters at Beseka Lake exceed the maximum permissible limit of suitability for irrigation. It is generally conceivable that the physicochemical characteristic of the Awash River varies in different water quality parameters at different sites. Only Beseka Lake and Meteka hot spring water exceeded pH and SAR permissible limit, and EC at Mojo, Wonji, Beseka, Melkasedi, Werer, Ambash, Meteka, and Meteka hot spring shows medium-to-high salinity scale, while RSC was very high at Beseka, Melkasedi, Meteka hot spring, Ambash, Meteka Mojo, Werer, Assayta, Wonji, Dupty, Tibila, Metehara, and Afambo, respectively. The establishment of wastewater treatment plants for industries and stormwater quality management at hotspot areas are recommended to improve the water quality, and dispatch proportion needs to be considered in the future.